The spiritual core of the hard problem: consciousness as foundational, not emergent - Arora, Amira (Frontiers in Psychology, 2025)
This paper proposes a transpersonal reframing of the Hard Problem of Consciousness by positing that consciousness is ontologically primary—not an emergent property of neural processes, but the foundational reality from which mind and matter arise. Integrating insights from non-dual spiritual traditions such as Advaita Vedanta and Tibetan Buddhism, contemplative science, and the work of transpersonal theorists including Jorge Ferrer, Ken Wilber, and Stanislav Grof, the study argues that a consciousness-centered metaphysics offers a more coherent model for explaining subjectivity, intentionality, and qualia. In critiquing materialist reductionism, it highlights the limitations of third-person methodologies and emphasizes the legitimacy of first-person and participatory ways of knowing. The paper also explores the broader epistemological, ethical, cultural, and ecological implications of adopting a transpersonal cosmology—one that bridges science and spirituality without collapsing their distinctions. By shifting the ontological center from matter to consciousness, this framework invites a pluralistic, integrative paradigm for understanding reality, advancing both human flourishing and scientific inquiry.